A grammar of trinitarian experience? On Sarah Coakley’s théologie totale - Khegan M. Delport (Verbum et Ecclesia)
The Anglican theologian Sarah Coakley has attempted to think trinitarian doctrine in explicitly experiential terms. Her erotically-charged, pneumatically-centred account of salvific incorporation attempts to articulate, on the one hand, an account of the purgation of desire and the senses through ascetic practice, contemplative prayer and liturgical habituation, while also maintaining, on the other hand, the priority of spiritual appetition as being itself the route through which believers are, gradually, drawn into the trinitarian life.